ETHICAL AND LEGAL ASPECTS OF ARTIFICIAL INTELLIGENCE IN ORAL HEALTH - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Alvin, Jonatan Deriano; Mayfrila, Angelina Alexandra; Cyntia, Wennie (HEARTY, 2025)
Integrating artificial intelligence (AI) into oral health has revolutionized diagnostics, treatment planning, and patient management. Despite its significant benefits, the adoption of AI introduces complex ethical and legal challenges that demand critical evaluation. This literature review explores AI applications' moral and legal implications in oral health, emphasizing patient privacy, data security, informed consent, and professional accountability. A systematic review of peer-reviewed journals and legal frameworks from 2016 to 2024 was conducted to analyze the current landscape. The findings highlight ethical dilemmas, including biases in AI algorithms, the need for equitable access to AI-based tools, and potential disruptions to dentist-patient relationships. Legal considerations, such as data protection laws and liability in AI-related errors, are also critically discussed. Addressing these challenges requires a collaborative approach involving healthcare professionals, legal experts, and policymakers. This review concludes that while AI holds transformative potential for oral health, addressing its ethical and legal challenges is essential to ensure responsible and sustainable implementation.